ANALISIS KOMPARATIF PRESTASI BELAJAR KELOMPOK PENERIMA KIP-K DAN REGULER PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNS - Nur Rohmah; Sudarno; Feri Setyowibowo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The purpose of this study was to gain an understanding of the differences between the learning achievement of groups that received KIP-K and those who did not and to identify the effect of interest in learning, achievement motivation, intelligence, family, and environment on student achievement. This study is a comparative study using quantitative methods involving 286 students as a population and 166 students as a sample from the FKIP UNS Economics Education study program. The purposive sampling method was used to select the sample. A Likert scale questionnaire was used as a data collection tool, and chi-square analysis was used to analyze the data. The research findings show that there is a significant difference in learning achievement between KIP-K recipients and regular groups with Sig. (2-tailed) of 0.000 < 0.05. Learning interest has a significant effect on regular group learning achievement with Asymptote scores. Sig (2-sided) of 0.022 < 0.05. Meanwhile, achievement motivation had a significant effect on the learning achievement of the KIP-K recipient group with an Asymptote value. Sig (2-sided) of 0.019 < 0.05. Meanwhile, intelligence, family, and environmental factors did not significantly affect the learning achievement of the KIP-K and regular recipient groups, as seen from the Asymp scores. Sig (2-sided) > 0.05.